Building strengths and skills a collaborative approach to working with clients - Corcoran, Jacqueline (Oxford : Oxford University Press, 2005)
Rather than identifying & 'fixing' perceived client weaknesses this book takes into account both individual resources & the areas where client skills can be bolstered, offering an eclectic practice approach that interweaves & operationalizes both strenghs-based & skills-based practice approaches.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social service; Mental health services; Counselor and client; Solution-focused therapy; Cognitive therapy